The first world war: A brief history with documents - Grayzel, Susan R. (Boston Bedford/St. Martin's, 2013)
Was a good book about the memoirs and letters of soldiers during the The Great War and not only from one country it gave the experience from other soldiers from France, Germany, Great Britain, and U.S. Good Book overall.
Index: p. 173 -182
Keywords: Tham khảo